Sinergi atau Konflik: Pasal 2 KUHP 2023 dalam Penegakan Hukum di Indonesia - Efendi, Nindy Putri Nur; Zulfa, Eva Achjani (Nagari Law Review, 2024)
Adat law is original Indonesian law, which lives and develops in society; the law is a social institution, therefore in its implementation, the law not only looks at legal rules but also looks at the effectiveness of these rules in the social field in society, in National criminal law reform has provided a breath of fresh air in the implementation of customary law in enforcing criminal law as contained in the provisions of Article 2 of the 2023 Criminal Code. The customary law that applies in Indonesia has differences between one region and another. This research is of a nature statute approach in which the research will examine the extent to which customary law can be used in national law as per the provisions in the 2023 Criminal Code. The provisions of Article 2 of the new Criminal Code have their pluses and minuses regarding the application of customary law in national law. The position of customary crimes in the 2023 Criminal Code as additional criminal penalties will place customary sanctions no longer as imperative but as facultative.